A Pictorial Review of CT Angiography Imaging Features of Aortic Dissection and Its Complications: Role of Emergency Teleradiology - Harika, Reddy Muni; Pallavi, Rao; Arjun, Kalyanpur (Journal of Clinical Interventional Radiology ISVIR, 2025)
Aortic dissection is an acute emergency affecting the aorta with a mortality of 50% in the first 48 hours of onset. The clinical outcome is determined by the type and extent of dissection, and its associated complications. Thus, knowledge of computed tomography (CT) angiography imaging features of aortic dissection and its complications, coupled with a process for immediate interpretation such as teleradiology, is essential for early diagnosis and treatment. The purpose of this study is to assess the imaging findings of aortic dissection and its complications on CT angiography and present a pictorial review of its imaging manifestations. We retrospectively evaluated 441 CT angiography studies diagnosed to have aortic dissection based on keyword search from emergency teleradiology reports. Noncontrast CT examinations were excluded from the study. The results were analyzed and compiled in a pictorial review. Aortic dissections are classified according to the Stanford classification system. Early diagnosis of aortic dissection and its complications is important in planning prompt management and avoiding fatal outcomes. CT angiography is a highly accurate noninvasive imaging investigation in the detection of aortic dissection and its complications. When coupled with emergency teleradiology analysis, the clinical outcomes can be significantly improved.
Keywords: aortic dissection; Stanford classification; teleradiology